Analisis Angka Harapan Hidup di Jawa Timur Tahun 2015 - Lina Septi Danasari; Arief Wibowo (Universitas Airlangga, 2017)
Life expectancy is one of the indicators to calculate the Human Development Index (HDI) which determined by infants’ health, toddlers’ health, frequency of liveborn children and death rate in the community. East Java Province has four dominant cultural areas such as Mataraman including the western part of the border of Central Java to Kediri, Madura including Bangkalan to Pamekasan, Arek including north coast of Surabaya to Malang and Tapal Kuda including Pasuruan, Probolinggo, Situbondo, Bondowoso, Lumajang and Jember. Those four cultural areas have different characteristic that can affect public health status especially life expectancy in East Java Province. The analysis aimed to know the correlation between infant mortality rate and life expectancy and to know the differences of life expectancy among four cultural areas in East Java year 2015. This analysis used secondary data obtained from Central Bureau of Statistic of East Java on May, 2017. The data were life expectancy as dependent variable, infant mortality rate as independent variable and cultural areas in East Java as grouping variables. The result showed that there was correlation between infant mortality rate with life expectancy (p=0.000) and there was different in life expectancy among four cultural areas in East Java year 2015 (p=0.000) such as cultural areas Mataraman-Madura, Mataraman-Tapal Kuda and Arek-Tapal Kuda. It suggested the government to continue improving the socio-economic welfare of the community and public health improvement in the Tapal Kuda area which had high infant mortality rate and low life expectancy.